2007
DOI: 10.1016/j.nlm.2007.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Life-long environmental enrichment differentially affects the mnemonic response to estrogen in young, middle-aged, and aged female mice

Abstract: The present study was designed to examine whether life-long exposure to standard or enriched housing affects the ability of estrogen to improve spatial and object memory throughout the lifespan. Three week-old female mice were maintained in standard or enriched housing up to and through ovariectomy and behavioral testing at 5, 17, or 22 months of age. Spatial memory was tested in the Morris water maze and object memory was tested using an object recognition task. Immediately after training each day, mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
70
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 87 publications
(154 reference statements)
11
70
0
1
Order By: Relevance
“…Novel object recognition, conducted as previously reported (29), evaluated nonspatial hippocampal memory (30). Briefly, mice were habituated to an empty white chamber by allowing them to freely explore for 5 min (no data were collected).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel object recognition, conducted as previously reported (29), evaluated nonspatial hippocampal memory (30). Briefly, mice were habituated to an empty white chamber by allowing them to freely explore for 5 min (no data were collected).…”
Section: Methodsmentioning
confidence: 99%
“…Time spent with each object was recorded; because mice inherently prefer to explore novel objects, a preference for the novel object [more time than chance (15 s) spent with the novel object] indicates intact memory for the familiar object. Vehicletreated mice remember the familiar object after 24 h, but not 48 h (29), and thus a 48-h delay is used to observe memory-enhancing effects of E 2 .…”
Section: Methodsmentioning
confidence: 99%
“…While some found significant positive effects on spatial memory only in aged mice 7 , other studies also demonstrated such effects in middle-aged mice 6 . Still, some studies have reported improvement on spatial task execution by both young and young adult mice groups 8,9,10,12 . However, studies conducted with mice in age groups similar to those used here did not find significant results for spatial memory tasks 7,8,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we did not obtain significant results, which is in accordance with studies that used similar housing periods ( from six to eight weeks) and complex EE protocols (cognitive and physical stimulation and social interaction) 7,8,15 . On the other hand, those studies with significant results in relation to spatial memory, despite using similar enrichment protocols, maintained the EE for longer periods, from 2 to 21 months 9,10,12 . Some of the groups that reported significant results with an EE period and enrichment protocol similar to this study 6,7,8 evaluated middle-aged and aged mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation